The inheritance of colonial penological practices in the postcolonial and apartheid periods: A histography of South Africa - Motlalekgosi, Hendrick Puleng (Technium Social Sciences Journal, 2022)
Colonialism has had an influence on many sectors across the board in South Africa including the prison system among others. Its impact could be seen in the way prisoners were treated during the post-colonial era and apartheid era. This paper seeks to demonstrate the relationship between the colonial, post-colonial and apartheid penological practices by examining the treatment of prisoners during the said periods. Examination of this relationship may be useful in understanding what really informed the promulgation of racist policies during the post-colonial period and apartheid period. This paper contends that the legislation that was promulgated during the post-colonial and apartheid periods, which were legislative instruments on how prisoners were treated, were in fact a formalization and continuation of what had already being practiced during the colonial era. The following themes are central to this discourse: The colonial period between the 1840s and 1909; The post-colonial period between 1910 and 1948 and; The National Party era (apartheid era): 1948 – 1993.